2011
DOI: 10.1002/ca.21280
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐anatomy of the renal sympathetic nervous system: A human postmortem histologic study

Abstract: Hypertension remains an epidemic uncontrolled with pharmacologic therapies. A novel catheter inserted into the renal artery has been shown to lower blood pressure by ablating the renal sympathetic nerves with radiofrequency energy delivered through the arterial wall. We report a histologic study describing the anatomic substrate for this technique, specifically the renal sympathetic nervous system. Histological sections from proximal, middle, and distal renal artery segments from nine renal arteries (five huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(90 citation statements)
references
References 14 publications
4
83
3
Order By: Relevance
“…10,13 Renal Neural Anatomy around the Renal Artery The renal plexus has been historically described as running circumferential around the renal artery based on cadaveric dissections and renal denervation procedures, 10,11,14 Two studies examining histological cross sections of 9 and 40 renal arteries confirms a circumferential distribution of nerves around the main renal artery. 15,16 However, there are more nerve fibers on the ventral aspect of the main renal artery compared to dorsal aspect (11.0±3.5 versus 6.2±3.0 per section, p<0.001). There is a significantly higher number of average nerve fibers per section on the proximal renal artery (39.6±16.7) compared to the distal renal artery (33.6±13.1) (p=0.01).…”
Section: Extrinsic Renal Nervesmentioning
confidence: 96%
See 1 more Smart Citation
“…10,13 Renal Neural Anatomy around the Renal Artery The renal plexus has been historically described as running circumferential around the renal artery based on cadaveric dissections and renal denervation procedures, 10,11,14 Two studies examining histological cross sections of 9 and 40 renal arteries confirms a circumferential distribution of nerves around the main renal artery. 15,16 However, there are more nerve fibers on the ventral aspect of the main renal artery compared to dorsal aspect (11.0±3.5 versus 6.2±3.0 per section, p<0.001). There is a significantly higher number of average nerve fibers per section on the proximal renal artery (39.6±16.7) compared to the distal renal artery (33.6±13.1) (p=0.01).…”
Section: Extrinsic Renal Nervesmentioning
confidence: 96%
“…15,16 The wall of a renal artery can have a depth up to 0.25mm, based on the upper bound 95% confidence interval of the tunica intima and media of the renal artery in an elderly subset of patients. 17 This suggests that nearly all of the nerve fibers, which are at least 0.5mm from the lumen, run outside of the tunica media and are in the tunica adventitia and surrounding tissue.…”
Section: Extrinsic Renal Nervesmentioning
confidence: 99%
“…Although some studies have suggested that the nerve fibers are relatively deep, 4 Atherton examined post mortem specimens and reported that 50% of renal nerves are located within 1 mm of the lumen and 90% less than 2 mm deep. 5 Investigators performed autopsies on 25 humans, identifying ten thousand nerves along the renal arteries. Less than 10% of these nerves were less than 1 mm deep.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Indeed, further careful evaluation done largely since the trial was completed has established that many of the critical nerve fibers-including the afferent fibers that conduct messages to the central nervous system-come into close prox-imity to the renal arteries mainly at distal sites, often in the vicinity of the bifurcation of the arteries. 7 As well, the potential importance of performing nerve ablations in accessory renal arteries is now becoming appreciated. Clearly, a more thorough ablation protocol must be tested in future trials.…”
Section: Lessons Learned From Symplicity Htn-3mentioning
confidence: 99%